PERANCANGAN APLIKASI SISTEM INFORMASI MEDIS MENGGUNAKAN BARCODE BERBASIS DESKTOP DAN ANDROID - Ida Bagus Surya Paramarta; Made Sudarma; Ida Bagus Alit Swamardika (Jurnal SPEKTRUM, 2017)
This research aims to design an applications of medical information system that uses barcode on desktop and Android device. Designing applications using Visual Basic, the Java programming language and MySQL for database system. In an application using the barcode type code 3 and 9. The process of data exchanged between device and database is done by using local networks to make distribution data easier. Application of medical information system using barcode-based desktop and Android created through several stages for designing system which is creation database system, barcode design, scanning barcode and development of the application of both in desktop and Android. The results of application medical information system use barcode based desktop and Android that is able to display information data of the patient to the doctor through the scan the barcode displayed on Android and desktop applications can update the information data of patients as well as doctors a Clinic Karya Prima.